Drought effects on soil greenhouse gas fluxes in a boreal and a temperate forest - Gillespie, L. M.; Kolari, P.; Kulmala, L.; Leitner, Sonja; Pihlatie, M.; Zechmeister-Boltenstern, S.; Díaz-Pinés, E. (Springer, 2024)
Changing water regimes (e.g. drought) have unknown long-term consequences on the stability and resilience of soil microorganisms who determine much of the carbon and nitrogen exchange between the biosphere and atmosphere. Shifts in their activity could feedback into ongoing climate change. In this study, we explored soil drought effects on soil greenhouse gas (GHG; CO2, CH4, N2O) fluxes over time in two sites: a boreal, coniferous forest in Finland (Hyytiälä) and a temperate, broadleaf forest in Austria (Rosalia). Topsoil moisture and topsoil temperature data were used to identify soil drought events, defined as when soil moisture is below the soil moisture at the permanent wilting point. Data over multiple years from automated GHG flux chambers installed on the forest floor were then analyzed using generalized additive models (GAM) to study whether GHG fluxes differed before and after drought events and whether there was an overall, multiyear temporal trend. Results showed CO2 and N2O emissions to be more affected by drought and long-term trends at Hyytiälä with increased CO2 emission and decreased N2O emissions both following drought and over the entire measurement period. CH4 uptake increased at both sites both during non-drought periods and as an overall, multiyear trend and was predominantly affected by soil moisture dynamics. Multiyear trends also suggest an increase in soil temperature in the boreal forest and a decrease in soil moisture in the temperate forest. These findings underline forests as an important sink for CH4, possibly with an increasing rate in a future climate.